The Evolution of Information Literacy Outcomes in Interdisciplinary Undergraduate Science Courses - Melanie Gainey; Neelam Bharti; Matthew Marsteller; Huajin Wang; Sarah Young; Michael Melville (Issues in Science and Technology Librarianship)
The ACRL Framework for Information Literacy presents opportunities for moving beyond ‘one-shot’ information literacy sessions and creating a more scaffolded and embedded approach for instruction. We collaborated with faculty at Carnegie Mellon University to create Framework-inspired information literacy learning objectives for first-year and third-year science undergraduates and are continuously refining the objectives as the curriculum continues to evolve. This article describes our learning objective design and refinement process, challenges encountered, and ideas on how to create opportunities for embedding information literacy into a curriculum. We also share our full activity lesson plans and assessment tool.